Results of kidney transplantation in University clinical centre Republic of Srpska in period from 2010-2018. - grujičić, milorad -; Žigić, Milan; Maksić, Milanko; Hajder, Slobodan; Golić, Darko; Gašić, Branislav; Rakanović, Dragan; Vasić, Novak; Laganin, Nataša; Roljić, Zoran; Stajčić, Ljubomir; Mišković, Mirjana; et al. (Scripta Medica, 2019)
Abstract Background/Aim. Kidney transplantation is the best treatment for patients with end-stage renal disease (ESRD). The aim of the study was to show the results of kidney transplantation performed in the University Clinical Center of the Republic of Srpska in the period 2010-2017     Methods. This was a retrospective, 8-year observational cross-sectional study. Studied endpoints were overall patient survival, as well as graft survival rate in kidney transplant recipients. Recipient's age, gender, induction immunosuppressive therapy, the underlying cause of ESRD, the dialysis modality and post-operative complications (surgical, medical, urinary tract infections (UTIs), electrolyte imbalance, and graft rejection) and their influence on the patient and graft survival rates were monitored. Results. The 30 living-donor kidney transplantations were performed, 29 living-related donor and 1 living-unrelated donor renal transplantation. 70% of kidney recipients were male, and 30% were female. The average age of patient was 34.43 ± 8.67 years. Induction immunosuppressive regimen was prescribed to 76.7% of transplanted patients. Graft rejection occurred in 5 patients (16.7%). The 1-year, 3-year, 5-year, and 8-year patients survival rates were 100%, 100%, 96.97% and 93.33%, respectively. Also 1-, 3-, 5-, and 8-year graft survival rates were 100%, 96.97%, 93.33% and 86.67%, respectively. The current mean value of glomerular filtration rate (GFR) in 25 patients with functional graft was 81.8 ± 30.3 mL/min. There was a statistically significant difference in the graft survival rate in the group with UTIs (66.66%) compared to a group without UTIs (100%). Overall patient survival was significantly shorter in the group with graft rejection (60%) compared to a group without graft rejection (92%). Kidney graft survival rate and overall patient survival have not been significantly different in terms of the studied factors (recipient’s age, gender, induction immunosuppressive treatment, underlying cause of ESRD, dialysis modality, surgical or medical complications, and electrolyte imbalance). Conclusion. The results of living-donor kidney transplantation performed in the University Clinical Center of the Republic of Srpska are good versus the results obtained at other centers. Key words: kidney transplantation; living donor; graft survival rate; patient survival rate Introduction